Genome-wide analysis of nuclear magnetic resonance metabolites revealed parent-of-origin effect on triglycerides in medium very low-density lipoprotein in PTPRD gene. (14th March 2018) - Pervjakova, N; Kukushkina, V; Haller, T; Kasela, S; Joensuu, A; Kristiansson, K; Annilo, T; Perola, M; Salomaa, V; Jousilahti, P; Metspalu, A; Mägi, R
Aim: The aim of the study was to explore the parent-of-origin effects (POEs) on a range of human nuclear magnetic resonance metabolites.Materials & methods: We search for POEs in 14, 815 unrelated individuals from Estonian and Finnish cohorts using POE method for the genotype data imputed with 1000 G reference panel and 82 nuclear magnetic resonance metabolites.Results: Meta-analysis revealed the evidence of POE for the variant rs1412727 in PTPRD gene for the metabolite: triglycerides in medium very low-density lipoprotein. No POEs were detected for genetic variants that were previously known to have main effect on circulating metabolites.Conclusion: We demonstrated possibility to detect POEs for human metabolites, but the POEs are weak, and therefore it is hard to detect those using currently available sample sizes.